EXPLOITING THE BIOCONTROL POTENTIAL OF ENTOMOPATHOGENIC NEMATODES IN COMBINATION WITH CHEMICALS AGAINST GREATER WAX MOTH (GALLERIA MELLONELLA L.) - M. Raheel1; N. Javed; S. A. Khan; S. Ahmed3. (Journal of Animal and Plant Sciences, 2017)
Entomopathogenic nematodes as alternatives to chemical pesticides for management of insect pests of various crop is an environmentally safe approach. Compatibility of Steinernema feltiae, S. asiaticum, Heterorhabditis bacteriophora and H. indica with seven chemical and biopesticides (imidacloprid (0.60 ml/L), spinosad (0.45 g/L), azadirachtin (1.5 ml/L), abamectin (1.25 ml/L), emamectin (0.20 ml/L), lambda-cyhalothrin (0.15 ml/L) and radiant (1.5 g/L) against Galleria mellonella was evaluated in lab. H. bacteriophora survived best as compared to all other entomopathogenic nematodes (EPN) species in all tested chemicals. S. feltiae survival was higher in imidacloprid followed by lambda-cyhalothrin, while abamectin proved to be lethal for S. feltiae. Azadirachtin and lambda-cyhalothrin proved to be compatible with H. bacteriophora as its survival was higher as compared to the rest of chemicals while radiant proved to be less friendly for its survival. Emamectin followed by abamectin were more compatible with S. asiaticum whereas radiant was least compatible. Exposure of H. indica to spinosad and emamectin resulted in greater survival of nematodes while survival was lower when applied with lambda-cyhalothrin and radiant. Survival of S. feltiae and H. bacteriophora was higher when compared to H. indica and S. asiaticum. The infectivity of S. feltiae was the maximum when used with imidacloprid and lambda-cyhalothrin. H. bacteriophora proved to be more compatible with imidacloprid, azadirachtin, emamactin and lambda-cyhalothrin. S. asiaticum and H. indica were compatible with emamectin. Among all tested chemicals, EPN species were sensitive to abamectin. These results showed that EPN species. with better compatibility with evaluated pesticides may be included in Integrated Pest Management (IPM) Programs.
Keywords: Compatibility; entomopathogenic nematodes; Steinernema feltiae; S. asiaticum; Heterorhabditis bacteriophora; H. indica; Galleria mellonella; chemicals; biopesticides